2022
DOI: 10.3389/fgwh.2022.869623
|View full text |Cite
|
Sign up to set email alerts
|

Preferences for Multipurpose Technology and Non-oral Methods of Antiretroviral Therapy Among Women Living With HIV in Western Kenya: A Survey Study

Abstract: IntroductionUnderstanding interests in and preferences for multipurpose technology (MPT) for the co-administration of contraception and antiretroviral therapy (ART) and alternative, non-oral ART methods among women living with HIV (WLHIV) is vital to successful implementation of future treatment options, such as long-acting injectable ART.MethodsBetween May 2016 and March 2017 we conducted a cross-sectional telephone survey of 1,132 WLHIV of reproductive potential with prior experience using intermediate- or l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…Another modeling study from South Africa found that provision of long-acting PrEP delivery to all HIV-negative injectable contraceptive users would be cost-effective at low drug prices, or when targeted to high-risk women [ 51 ]. As with previous research [ 46 48 ], preferences for MPTs in our study diminished under circumstances where side-effects (including menstrual changes) were greater with a dual-protection than a single indication product, and with formats that could not be stopped/removed if dual-protection was no longer needed or desired, highlighting trade-offs of choosing an MPT product. However, dual-protection products are unlikely to have more side effects than two separate single-indication products administered together.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Another modeling study from South Africa found that provision of long-acting PrEP delivery to all HIV-negative injectable contraceptive users would be cost-effective at low drug prices, or when targeted to high-risk women [ 51 ]. As with previous research [ 46 48 ], preferences for MPTs in our study diminished under circumstances where side-effects (including menstrual changes) were greater with a dual-protection than a single indication product, and with formats that could not be stopped/removed if dual-protection was no longer needed or desired, highlighting trade-offs of choosing an MPT product. However, dual-protection products are unlikely to have more side effects than two separate single-indication products administered together.…”
Section: Discussionsupporting
confidence: 81%
“…Development of multi-purpose prevention technologies (MPTs) has accelerated in recent years, with several products in the development pipeline including both long-acting and on-demand options [ 44 , 45 ]. MPTs have the potential to both better appeal to target end-users ( 46 48 ) and to be cost-effective [ 49 ] relative to single-indication products. A recent costing study found that MPTs, including long-acting injectable antiretrovirals (ARVs), would likely be cost-effective among female sex workers and young women ages 16–24 in South Africa [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…FSW wanted duration of protection consistent with injectable contraception. Other user groups, such as women living with HIV, have also identified a longer-acting injectable as preferred over daily oral tablets when a multipurpose technology concept offered an antiretroviral for HIV treatment co-administered with a hormonal contraceptive ( 40 ). However, this may reflect respondent bias in that injectable contraception is well accepted in Kenya, thereby making it a familiar benchmark technology.…”
Section: Discussionmentioning
confidence: 99%